2010
DOI: 10.5194/acp-10-5925-2010
|View full text |Cite
|
Sign up to set email alerts
|

Optical, physical and chemical characteristics of Australian continental aerosols: results from a field experiment

Abstract: Abstract. Mineral dust is one of the major components of the world's aerosol mix, having a number of impacts within the Earth system. However, the climate forcing impact of mineral dust is currently poorly constrained, with even its sign uncertain. As Australian deserts are more reddish than those in the Northern Hemisphere, it is important to better understand the physical, chemical and optical properties of this important aerosol. We have investigated the properties of Australian desert dust at a site in SW … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 63 publications
(68 reference statements)
1
37
0
Order By: Relevance
“…Aerosol sources contributing to the noted rise during spring are heterogeneous, with suggested contributions from fine aeolian dust , a combination of biomass burning smoke, fine dust, and maritime aerosol from long-range transport (Radhi et al, 2010), and exogenous biomass burning aerosol originating in southern Africa or even South America (Rosen et al, 2000).…”
Section: Amplitude and Phase Of The Aerosol Optical Depth Of Harmonicmentioning
confidence: 99%
“…Aerosol sources contributing to the noted rise during spring are heterogeneous, with suggested contributions from fine aeolian dust , a combination of biomass burning smoke, fine dust, and maritime aerosol from long-range transport (Radhi et al, 2010), and exogenous biomass burning aerosol originating in southern Africa or even South America (Rosen et al, 2000).…”
Section: Amplitude and Phase Of The Aerosol Optical Depth Of Harmonicmentioning
confidence: 99%
“…Almost all published experimental studies on CCN activity of fresh dust (e.g., Koehler et al, 2009;Herich et al, 2009) parameterize laboratory observations using the KT framework on the assumption that dust CCN activity is controlled solely by the amount of soluble salts in the mineral aerosol, with the insoluble fraction not affecting water activity. However, studies that measured soluble ions composition on dust samples collected from various dust source regions (e.g., Song et al, 2005;Radhi et al, 2010) indicated negligible amounts of soluble salts. In a recent study, Kumar et al (2011) compared the power law exponent derived from the experimental s c −D dry relationship with those determined from FHH-AT and KT, and suggested that FHH-AT is a better representation than KT for CCN activity of dry generated dust devoid of a soluble fraction.…”
Section: Introductionmentioning
confidence: 99%
“…Australian dust particle size and colour is different from the Northern Hemisphere 'dust belt' (Kiefert et al, 1996;Qin and Mitchell, 2009;Radhi et al, 2010). For example, a greater fraction of larger particles has been found for Australian dust compared to African dust (Kiefert et al, 1996), suggesting that the optical properties of dust from Australia are different from the Sahara.…”
Section: Introductionmentioning
confidence: 94%
“…Recent field campaigns for identifying mineral composition of Australian dust (e.g. Qin and Mitchell, 2009;Radhi et al, 2010) have also contributed. Lake Eyre Basin of central eastern Australia is the most important source of mineral dust in the Southern Hemisphere, with an average of 82 dusty days per year (Bullard and McTainsh, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation